Research of Local People’s Attitudes toward the Syrians in Turkey: A Case Study of Kahramanmaraş - Bekir Güzel (Sosyal Siyaset Konferansları Dergisi)
Since the 2000s, international migration toward Turkey has been increasing. Particularly, because of the mass asylum requests on the Syrian border since 2011; in the present day, nearly four million Syrians live in Turkey. Here, a survey design was used to examine the attitudes of local people in Kahramanmaraş toward the Syrians. The “attitude scale of local people toward Syrians” developed by Özüdoğru, Kan, Uslu, and Yaman (2018) was used. Data collection was conducted using the convenience sampling method, and 405 participants were interviewed between 20 August and 30 November 2020. The data were collected from local people who volunteered to participate in the research and resided in Kahramanmaraş. As per the study results, it was determined that the local people’s attitude score toward Syrians did not show a significant difference (p>0.05) according to their gender, marital status, age groups, employment status, the number of members in their family, and hometown. However, a significant difference (p<0.05) in the attitude score of local people toward Syrians according to their education level, profession, and monthly income was revealed. Thus, the attitude score of the local people toward Syrians is at a low level. When it comes to issues, such as living together and social cohesion, the perspectives of both the local people and the migrant population must be positive. Therefore, studies that will positively improve both parties’ perception (emotion and thought) and attitude (behavior) are needed. At this point, various social, cultural, or religious activities, such as “cohesion neighborhood meetings” (kermesses/bazaars, festivals, celebrations, feasts, kandils, or blessed nights) can be expanded.